Mechanical characterization of Araldite LY 564 epoxy: creep, relaxation, quasi-static compression and high strain rate behaviors - Bakbak, Okan; Birkan, Besim Emre; Acar, Alperen; Colak, Ozgen (SPRINGER, 2022)
A comprehensive mechanical characterization of a commercially available hot curing epoxy system (Araldite(R) LY 564 with Aradur(R) 2954, HUNTSMAN Corp.) is performed including compression tests at quasi-static and high strain rates, as well as creep and relaxation tests. High strain rate tests (770/s and 875/s) are conducted by using a split-Hopkinson pressure bar (SHPB) apparatus and compared with the quasi-static compression tests at three strain rates (0.001/s; 0.01/s; 0.1/s). Elasticity modulus and yield stress increase with increasing strain rate, for both quasi-static and high strain rate conditions. The change in the mechanical behavior from quasi-static to high strain rate conditions is quite prominent. While strain rate changes from 0,001/s to 875/s, elasticity modulus increases from 1465 to 3193 MPa (118% increase) and yield stress from 119 to 204 MPa (72% increase). The evident exponential hardening at the viscoplastic region seen on quasi-static stress-strain curves is not observed at high strain rates. Creep tests are performed for three different stress levels (50, 100 and 200 MPa) and 120 min (7200 s). In addition, relaxation tests are done for three different strain levels (3.16, 7.15 and 35.5%) also for 120 min (7200 s). Creep compliance and relaxation modulus are calculated and plotted. It is observed that creep strain values at the stress levels lower than the yield point are lesser compared to creep strain values around yield strength since rate dependency is increasing with increasing stress. Creep at the hardening region is not prominent due to polymer chain entanglement. Stress drop during relaxation is increasing with the increasing strain level.
Keywords: Epoxy; SHPB; Compression; Creep; Relaxation; Polymer Science